2004
DOI: 10.1002/art.20132
|View full text |Cite
|
Sign up to set email alerts
|

Potential strategies to reduce medial compartment loading in patients with knee osteoarthritis of varying severity: Reduced walking speed

Abstract: Objective. To determine whether reducing walking speed is a strategy used by patients with knee osteoarthritis (OA) of varying disease severity to reduce the maximum knee adduction moment.Methods. Self-selected walking speeds and maximum knee adduction moments of 44 patients with medial tibiofemoral OA of varying disease severity, as assessed by using the Kellgren/Lawrence grade, were compared with those of 44 asymptomatic control subjects matched for sex, age, height, and weight.Results. Differences in self-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
271
7
9

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 380 publications
(311 citation statements)
references
References 20 publications
20
271
7
9
Order By: Relevance
“…2-B). The relationship between the high adduction moments and thinner cartilage in patients with osteoarthritis of the knee is consistent with the findings of clinical studies, which suggest that the adduction moment during walking can be predictive of the clinical outcome of treatment 11 , disease severity 12,13 , and disease progression 14 for medialcompartment osteoarthritis of the knee. The contrasting results for the healthy knee and the osteoarthritic knee suggest that healthy cartilage responds positively to load, whereas degraded cartilage in osteoarthritic knees responds negatively to load.…”
Section: Cartilage Morphology and Walking Mechanicssupporting
confidence: 82%
“…2-B). The relationship between the high adduction moments and thinner cartilage in patients with osteoarthritis of the knee is consistent with the findings of clinical studies, which suggest that the adduction moment during walking can be predictive of the clinical outcome of treatment 11 , disease severity 12,13 , and disease progression 14 for medialcompartment osteoarthritis of the knee. The contrasting results for the healthy knee and the osteoarthritic knee suggest that healthy cartilage responds positively to load, whereas degraded cartilage in osteoarthritic knees responds negatively to load.…”
Section: Cartilage Morphology and Walking Mechanicssupporting
confidence: 82%
“…Seven studies (29 -35) evaluated the effect of increasing toe-out, 3 of which also evaluated reducing toe-out (31)(32)(33). Alteration of gait speed was also investigated, with 7 studies evaluating increasing speed (36 -42) and 4 studies investigating reduced speed (36,39,40,42). Gait aids were investigated in 3 studies, 2 of which evaluated contralateral cane use (43,44), 1 investigated ipsilateral cane use (43), and 1 examined Nordic walking poles (45).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the knee adduction moment during walking is associated with the presence [2,42] and rate of progression [36] of medial compartment knee osteoarthritis (OA) and has been used to predict the outcome of treatment interventions for OA [45]. Clinical and analytic studies [1,46] associate external adduction moment with excessive loading of the medial compartment.…”
Section: Orthoticsmentioning
confidence: 99%